In vitro hepatic microsomal metabolism of N-benzyl-N-methylaniline - (:unkn) unknown (ELSEVIER SCIENCE SA, 1999)
In the present study, the in vitro microsomal metabolism of a tertiary aniline, N-benzyl-N-methylaniline (NBNMA) was studied to determine whether this compound produces an amide derivative (benzoyl) together with N-dealkylation and C- and N-oxidation products as metabolites. The preparations of the corresponding potential metabolites were undertaken and were separated using TLC and HPLC. Incubations were performed using rat microsomal preparations fortified with NADPH. The substrate and its potential metabolites were extracted into dichloromethane in the presence of NaCl and examined by TLC and HPLC-UV. The results indicated that NBNMA did not produce the corresponding amide (benzoyl derivative) or N-oxide metabolite but was dealkylated to the corresponding secondary amine. Two p-hydroxylated phenolic metabolites were also observed. These findings support the concept that nitrones are essential intermediate metabolites for the formation of amides from secondary aromatic amines (chemical rearrangement to amide via an oxaziridine intermediate). The carbinolamine produced from NBNMA does not seem stable enough to allow further oxidation to the amide and therefore this intermediate is broken down to the dealkylation products. N-Dealkylations and p-hydroxylations are major metabolic reactions following in vitro hepatic microsomal metabolism of the benzylic tertiary aniline, NBNMA. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: microsomes; metabolism; tertiary anilines; amide formation; BENZYLANILINES